2004
DOI: 10.1563/0.674.1
|View full text |Cite
|
Sign up to set email alerts
|

Implant Biomechanics in Grafted Sinus: A Finite Element Analysis

Abstract: This in vitro study investigated the stress distribution in the bone surrounding an implant that is placed in a posterior edentulous maxilla with a sinus graft. The standard threaded implant and anatomy of the crestal cortical bone, cancellous bone, sinus floor cortical bone, and grafted bone were represented in the 3-dimensional finite element models. The thickness of the crestal cortical bone and stiffness of the graft were varied in the models to simulate different clinical scenarios, representing variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 19 publications
3
36
0
1
Order By: Relevance
“…Decrease in stresses in a 7-mm native bone model in comparison with 3-4-mm models were found and similar values were obtained with 10-mm models. Present findings related to increase in bone strains under laterally axial loading was consistent with findings of other studies [9,15,16].…”
Section: Dıscussıonsupporting
confidence: 93%
“…Decrease in stresses in a 7-mm native bone model in comparison with 3-4-mm models were found and similar values were obtained with 10-mm models. Present findings related to increase in bone strains under laterally axial loading was consistent with findings of other studies [9,15,16].…”
Section: Dıscussıonsupporting
confidence: 93%
“…A number of finite element analysis studies showed, that when axial and lateral physiologic forces are applied to the implant, high peak stresses are generated in cortical bone (Fanuscu et al 2004;Himmlova et al 2004;Tada et al 2003). Other in vitro studies show, that loss or absence of cortical bone results in stress transfer to cancellous bone, whose stiffness is 10 times lower, than cortical bone and may not be able to withstand the stresses subjected to the implant, resulting in implant destabilization and subsequent loss (Watzek G. 2004).…”
Section: I31 A) Early Crestal Bone Lossmentioning
confidence: 99%
“…FE models with complex geometric structures can be easily modified to accommodate various assumptions. The quality of the FE model is determined by its concurrence with anatomical and natural conditions [2,11,13,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…For cortical bone, compact bone and bone grafts, Young's modulus is 14 GPa and Poisson's ratio µ = 0.30. For titanium alloy, Young's modulus is 103.4 GPa and Poisson's ratio µ = 0.35 [13].…”
Section: Contact Definitionmentioning
confidence: 99%